Cellular localization of cyclo-oxygenase isozymes in Crohn’s disease and colorectal cancer - Müller-Decker, Karin; Marks, Friedrich; Fürstenberger, Gerhard (International journal of colorectal disease, 1999)
Deregulation of cyclo-oxygenase isozyme expression has been shown to be a consistent feature of inflammatory bowel diseases and colorectal cancer in humans. This study investigated the cellular localization of aberrant cyclo-oxygenase expression in normal and diseased colon. Biopsies of seven normal colonic tissues, eight tissue samples from patients suffering from Crohn’s disease, five polyps from patients with familiar adenomatous polyposis coli, and ten sporadic adenocarcinomas were analyzed using isozyme-selective immunoprecipitation, western blotting, and immunohistochemistry. Cyclo-oxygenase-1 expression was demonstrated in normal human colon, Crohn’s disease, and colorectal tumors. In normal colon and also in adenomatous polyps, cyclo-oxygenase-1 specific immunosignals were localized to epithelial cells of the upper part of the crypts and endocrine cells of the lower part. In Crohn’s disease cyclo-oxygenase-1 expression was restricted to cells of the inflammatory infiltrate. While barely detectable in normal colon, cyclo-oxygenase-2 protein was strongly increased in epithelial cells located in the uppermost part of the crypts, in surface epithelial cells, and in mononuclear cells of the lamina propria of Crohn’s disease. The constitutive overexpression of cyclo-oxygenase-2 protein observed in the majority of the adenomatous polyps and all adenocarcinomas was attributed to both epithelial and interstitial cells in that the latter predominated in adenomas, and epithelial cells were the prevailing cyclo-oxygenase-2 expressing cell type in adenocarcinomas. In conclusion, both autocrine and paracrine effects of aberrant cyclo-oxygenase-2 expression may contribute to the development of Crohn’s disease and colonic tumor development.